Safety Assessment of Ultrasound-Assisted Intravesical Chemotherapy in Normal Dogs: A Pilot Study - Sasaki, Noboru; Ikenaka, Yoshinori; Aoshima, Keisuke; Aoyagi, Teiichiro; Kudo, Nobuki; Nakamura, Kensuke; Takiguchi, Mitsuyoshi (Frontiers in Pharmacology, 2022)
Intravesical chemotherapy after transurethral resection is a treatment option in patients with non-muscle invasive bladder cancer. The efficacy of intravesical chemotherapy is determined by the cellular uptake of intravesical drugs. Therefore, drug delivery technologies in the urinary bladder are promising tools for enhancing the efficacy of intravesical chemotherapy. Ultrasound-triggered microbubble cavitation may enhance the permeability of the urothelium, and thus may have potential as a drug delivery technology in the urinary bladder. Meanwhile, the enhanced permeability may increase systemic absorption of intravesical drugs, which may increase the adverse effects of the drug. The aim of this preliminary safety study was to assess the systemic absorption of an intravesical drug that was delivered by ultrasound-triggered microbubble cavitation in the urinary bladder of normal dogs. Pirarubicin, a derivative of doxorubicin, and an ultrasound contrast agent (Sonazoid) microbubbles were administered in the urinary bladder. Ultrasound (transmitting frequency 5 MHz; pulse duration 0.44 μsec; pulse repetition frequency 7.7 kHz; peak negative pressure −1.2 MPa) was exposed to the bladder using a diagnostic ultrasound probe (PLT-704SBT). The combination of ultrasound and microbubbles did not increase the plasma concentration of intravesical pirarubicin. In addition, hematoxylin and eosin staining showed that the combination of ultrasound and microbubble did not cause observable damages to the urothelium. Tissue pirarubicin concentration in the sonicated region was higher than that of the non-sonicated region in two of three dogs. The results of this pilot study demonstrate the safety of the combination of intravesical pirarubicin and ultrasound-triggered microbubble cavitation, that is, ultrasound-assisted intravesical chemotherapy.